PERANAN AUDIT INTERNAL DALAM PENGENDALIAN RISIKO PEMBIAYAAN DI BANK BRI SYARIAH KANTOR CABANG DIPONEGORO SURABAYA - Khayat, Ismatul (Akuntansi : Jurnal Akuntansi Integratif, 2015)
The study, entitled "The Role of Internal Audit in Risk Control Financing Bank BRI Syariah Branch Office Diponegoro Surabaya" This is the result of a qualitative study aimed to answer the question of how the internal audit mechanisms in financing and how the role of internal audit in controlling risks in the financing of Bank BRI Syariah Office Diponegoro Surabaya branch. The methodology used in this study is a qualitative method case study on the object under study. Data collection was conducted research by interviewing informants internal audit team and employees of Bank BRI Syariah Branch Office Diponegoro Surabaya. The data is then analyzed by inductively mindset which means mindset that is grounded in the facts are specific, then studied, analyzed and summarized into solving the problems or solutions that can be applied generally. The results showed that, the internal audit mechanism in finance at Bank BRI Syariah Branch Office Diponegoro Surabaya include audit preparation phase, the phase of the audit program, the stage of implementation of audit, audit reporting stage, the stage of follow-up results of the audit and the stage of documentation and administration, and second, the role of internal audit in controlling the financing risks are classified in the role of problem solver, compliance role, the role of negotiator and the role that such controls contained in the audit report. On the mechanism of internal audit, the auditor should prepare in advance of key risk mitigation data based Al-Daulah Vol. 1, No. 1, April 2015 16 Ismatul Hayati financing, taking samples financing completed in financing the collectability of 3 to 5 and propagated back to the financing Collectable 1 and 2. To that end, each bank can increase the audit team for more funding audited, so that a more comprehensive risk control on all funding channeled bank. In the role of internal audit, internal audit will be instrumental if the creditor or LHA written more specific recommendations for the auditee to improve their performance. So that the internal audit more direct role in the change of attitude of the auditee in carrying out the responsibilities and authority.